A new open-pit mine planning optimization method using block aggregation and integer programming - N.L. Mai; E. Topal; O. Erten (My University, 2018)
The authors propose a two-stage method: first, a novel TopCone algorithm (TCA) clusters mining blocks into cone-shaped aggregates (TopCones) with explicitly controlled cluster count; second, these TopCones are used in an integer programming model with operational constraints to optimize long-term production scheduling. A case study on a large-scale copper deposit shows that this method achieves higher NPV than commercial software, and completes optimization within minutes.
Keywords: large-scale optimization; TopCone algorithm; production scheduling; open pit mine planning; integer programming